Muscle metabolism and impaired sprint performance in an elite women's football game - Krustrup, P.; Mohr, M.; Nybo, L.; Draganidis, D.; Randers, M. B.; Ermidis, G.; Oerntoft, C.; Røddik, L.; Batsilas, D.; Poulios, A.; Ørtenblad, N.; Loules, G.; et al. (Scandinavian Journal of Medicine & Science in Sports, 2021)
The present study examined skeletal muscle metabolism and changes in repeated sprint performance during match play for n = 20 competitive elite women outfield players. We obtained musculus vastus lateralis biopsies and blood samples before, after, and following intense periods in each half of a friendly match, along with 5 × 30-meter sprint tests and movement pattern analyses (10-Hz S5 Global Positioning System [GPS]). Muscle glycogen decreased by 39% and 42% after an intense period of the second half and after the match, respectively, compared to baseline (p < 0.05). Post-match, 80% type I fibers and 69% type II fibers were almost empty or completely empty of glycogen. Muscle lactate was higher (p < 0.05) after the intense period of the first half and post-match compared to baseline (14.3 ± 4.6 (±SEM) and 12.9 ± 5.7 vs. 6.4 ± 3.7 mmol/kg d.w.). Muscle phosphocreatine was reduced (p < 0.05) by 16% and 12%, respectively, after an intense period in the first and second half compared to baseline. Blood lactate and glucose increased during the match and peaked at 8.4 ± 2.0 and 7.9 ± 1.2 mmol/L, respectively. Mean 5 × 30 m sprint time declined by 3.2 ± 1.7 and 7.0 ± 2.1% after the first and second half, respectively, and 4.7 ± 1.6% (p < 0.05) after an intense period in the first half compared to baseline. In conclusion, match play in elite female football players resulted in marked glycogen depletion in both fiber types, which may explain fatigue at the end of a match. Repeated sprint ability was impaired after intense periods in the first half and after both halves, which may be associated with the observed muscle metabolite perturbations.